Implementation Of Marketing Aspects In Management Information Systems In E-Commerce Strategy Of Hybrid And Virtual Sales At Star Skincare In Surabaya (Perak, Pabean Cantian District) - Najla Shafaa Kamila; Abdur Rohman (Penerbit Hellow Pustaka, 2025)
The development of an increasingly demanding era brings various types of technology. Almost all fields of human work that use information and communication technology that change people's lives require very fast and accurate information exchange. Star Skincare is a skincare sales company based in Surabaya. Nowadays skin care has grown rapidly in society. In this case, the e-commerce strategy has a huge impact on the rights of the distributor. Star Skin Care's skincare sales marketing strategy uses a hybrid sales system and virtual sales. The purpose of this study is to evaluate how the e-commerce sales system at Star Skin Care currently works. Then the customer's perspective can be restored so that recovery can be achieved in terms of the services carried out and the creation of customer satisfaction.The method used in this study is qualitative to describe and explain the state being studied. The existence of hybrid and virtual delivery systems makes it easier for people to obtain information when transacting.